Management of Sandhigata Vata with Janudhara and Lepa - A Case Study: Life Sciences - Pipare, Prashish; Nibrad, Chitraveena; Parwe, Shweta (International Journal of Life Science and Pharma Research, 2023)
SandhigataVata is a disorder where Vata dosha is dominant. In particular, SandhigataVatais the changes the inflammation and degeneration in joints. The condition gets tedious when joints like Janusandhi (knee joint) which is a mobile joint, the body gets involved in SandhigataVata. There is more prevalence in overweight patients because, among all the joints, it is the weightbearing joint. The dominance of Vata Dosha is central to the pathogenesis of Sandhigatavata. It can be considered a musculoskeletal abnormality according to modern science. To evaluate the efficacy of dashmool tailjanudharaand Lepa(Shunthi and Haridra) in Sandhigatvatavata. To study the effectiveness of Ayurvedic management with Panchakarma and ShamanaChikitsa (palliative therapy) in Sandhigatavata. A55 years old female individual was diagnosed as SandhigataVata with symptoms of pain, swelling in the right knee joint, and difficulty while walking for one year. There were osteophyte changes in the X-ray of the right knee common. The management plan includes panchakarma in which local abhyanga(massage), Local Swedana with Nadisveda(hot fomentation), Janudhara(oil pouring),andlepa was advised ShamanchikitsaincludedHingwashtakchurna, YogarajGuggulu, and Avipattikarachurna. Pain, Swelling, and difficulty in walking were reduced markedly.:The patient got adequate relief in clinical features; she could walk correctly.